Catalyst Decomposition during Olefin Metathesis Yields Isomerization‐Active Ruthenium Nanoparticles. Issue 15 (28th July 2016) - Higman, Carolyn S.; Lanterna, Anabel E.; Marin, M. Luisa; Scaiano, Juan C.; Fogg, Deryn E.
Abstract: The second‐generation Grubbs catalyst, RuCl2 (H2 IMes)(PCy3 ) (=CHPh) [GII ; H2 IMes=1, 3‐bis(2, 4, 6‐trimethylphenyl)‐4, 5‐dihydroimidazol‐2‐ylidene, Cy=cyclohexyl], is shown to decompose during olefin metathesis to generate Ru nanoparticles (RuNPs). These RuNPs appear to contribute significantly to competing isomerization during metathesis. Larger, partially oxidized RuNPs are also observed in commercialGII, but these exhibit modest isomerization activity. Removal of RuNPs from the precatalyst does not prevent isomerization, because new, more reactive NPs are generated by catalyst decomposition during metathesis. Abstract : Nanoparticles in metathesis : A previously unrecognized decomposition pathway is reported for the Grubbs catalyst, which results in the formation of isomerization‐active nanoparticles (NPs). Cy=cyclohexyl, H2 IMes=1, 3‐bis(2, 4, 6‐trimethylphenyl)‐4, 5‐dihydroimidazol‐2‐ylidene.